Randomized phase II trial of S‐1 plus cisplatin or docetaxel plus cisplatin with concurrent thoracic radiotherapy for inoperable stage III non‐small cell lung cancer. (14th December 2020) - Shimokawa, Tsuneo; Yamada, Kazuhiko; Tanaka, Hiroshi; Kubota, Kaoru; Takiguchi, Yuichi; Kishi, Kazuma; Saito, Haruhiro; Hosomi, Yukio; Kato, Terufumi; Harada, Daijiro; Otani, Sakiko; Kasai, Takashi; et al.
Abstract: Cisplatin‐based chemoradiotherapy is considered standard treatment for unresectable locally advanced non‐small‐cell lung cancer (LA‐NSCLC). This study examined two regimens of chemotherapy in concurrent chemoradiation. Eligible patients with unresectable, radically irradible LA‐NSCLC were randomized to either the SP (S‐1 and cisplatin) or DP (docetaxel and cisplatin) arms with concurrent thoracic radiotherapy of 60 Gy, comprising 2 Gy per daily fraction. The primary endpoint was the overall survival (OS) rate at 2 years (the 2‐year OS rate). From May 2011 to August 2014, 110 patients were enrolled. Of 106 eligible patients, the 2‐year OS rates were 79% (95% CI: 66%–88%) and 69% (95% CI: 55%–80%) the SP and DP arms, respectively. The median progression‐free survival was 11.6 months for the SP arm and 19.9 months for the DP arm, while the median survival time was 55.2 months for the SP arm and 50.8 months for the DP arm. Grade 3/4 leukopenia were more frequent in DP arm. The incidences of febrile neutropenia and pneumonitis tended to be higher in DP arm. There were no treatment‐related deaths in either arm. The primary endpoint was met in both arms. The SP arm as a future reference regimen will be chosen due to fewer toxicities and better OS. Abstract : This trial evaluated two experimental regimens that combine chemotherapy with concurrent radiotherapy. The S‐1 and cisplatin arm as a future reference regimen will be chosen due to fewer toxicities and better overall survival.